The Effect of Interpersonal Communication and Organizational Trust on Employee Engagement and Their Impact on Job Performance - Maslikha, Isna; Achmad Fauzi; Dedi Sutomo; Mohammad Reza Fakhruddin (Dinasti International Journal of Economics, Finance & Accounting, 2022)
This pre-research was conducted with the aim of building a research hypothesis using a descriptive method. In knowing the variables that affect Employee Engagement and Job Performance, a review of previous research is carried out. The preparation of this article for the authors is intended to build hypotheses in seeking influence among several variables that can be used as objects of further research. The results of writing this article show that: 1) Interpersonal Communication has an influence on Employee Engagement; 2) Interpersonal Communication influences Job Performance; 3) Organizational Trust affects Employee Engagement; 4) Organizational Trust has an influence on Job Performance; 5) Employee Engagement has an influence on Job Performance.